Selection of suitable growing substrates and quality assessment of Brassica microgreens cultivated in greenhouse - Hoang, Gia Minh; Vu, Thuong Thi (Academia Journal of Biology, 2022)
Brassica microgreens are typically cultivated using a peat-based growing substrate with a higher production cost as this substrate must be imported from overseas. In Vietnam, a source of local bio-materials that could be used to replace imported peat, resulting in more affordable growing substrates. Several growing substrates for Brassica microgreens were evaluated in this study: GT1 (30% sand +20% organic soil + 50% coco coir), GT2 (75% coco coir + 25% rice husk), GT3 (75% coco coir + CaO 2.2 mg/kg + acid humic 0.41%) and imported peat GT4 (75% white sphagnum peat +25% vermiculite (size 4–6 mm). The local organic material coco coir GT3 was found to be as effective as the imported substrate for microgreen production. The material coco coir mixed with soil and sand could increase the risks of soil-borne disease infestation on Brassica microgreens. Microgreens grown in the substrate GT3 and GT4 had higher productivity and lower disease infestation levels than other tested substrates. Nitrate level and microbiological contamination (E. coli and Salmonella spp.) of Brassica microgreens cultivated in these substrates were determined to be at safe levels.